Sociodrama Training to Improve Social Interaction Skills in MAN 1 Students Ternate City: Pelatihan Sosiodrama untuk Meningkatkan Keterampilan Interaksi Sosial pada Siswa MAN 1 Kota Ternate - Roni Kurniawan; Iwan Abdy (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
In the era of globalization and rapid technological advancement, social interaction skills play a vital role in shaping students’ character and social competence. The dominance of digital communication has reduced the quality of direct interactions, especially among madrasah students. In Ternate’s cultural context, which values social harmony and togetherness, this decline presents a challenge that requires contextually relevant educational strategies. Sociodrama—an active learning method involving role-play in simulated social scenarios—has proven effective in enhancing students’ social abilities. Responding to this need, the Community Service Team from the Faculty of Teacher Training and Education (FKIP), Universitas Khairun, organized a Sociodrama Training program at MAN 1 Kota Ternate on July 17–18, 2025. The training aimed to improve students’ social interaction skills and was conducted at the university’s partner school. The outcomes are expected to be integrated into regular school learning to strengthen students’ character development and interpersonal competencies in a sustainable manner.